2016
DOI: 10.1007/s10637-016-0387-y
|View full text |Cite
|
Sign up to set email alerts
|

The novel kinase inhibitor ponatinib is an effective anti-angiogenic agent against neuroblastoma

Abstract: Background High-risk neuroblastoma has poor outcomes with high rates of relapse despite aggressive treatment, and novel therapies are needed to improve these outcomes. Ponatinib is a multi-tyrosine kinase inhibitor that targets many pathways implicated in neuroblastoma pathogenesis. We hypothesized that ponatinib would be effective against neuroblastoma in preclinical models. Methods We evaluated the effects of ponatinib on survival and migration of human neuroblastoma cells in vitro. Using orthotopic xenograf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…Recently, it has been suggested that the use of reduced doses of ponatinib (down to 15 mg/day instead of the usual dosage of 45 mg/day) might maintain therapeutic activity in most patients while decreasing the vascular adverse events (24,26). Although clinicians will have to tackle the side effects observed upon ponatinib administration, the results achieved through our study, as well as others (17,18), indicate that this drug has the potential to be employed in clinical trials aimed to evaluate benefits in high-risk NB patients.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Recently, it has been suggested that the use of reduced doses of ponatinib (down to 15 mg/day instead of the usual dosage of 45 mg/day) might maintain therapeutic activity in most patients while decreasing the vascular adverse events (24,26). Although clinicians will have to tackle the side effects observed upon ponatinib administration, the results achieved through our study, as well as others (17,18), indicate that this drug has the potential to be employed in clinical trials aimed to evaluate benefits in high-risk NB patients.…”
Section: Discussionsupporting
confidence: 50%
“…Although we could not prove a significant activity of axitinib in our in vivo model, one previous study indicated that axitinib could partially impair the growth of human NB xenografts by inhibiting angiogenesis (16). Notably, independent investigations have very recently proposed ponatinib itself as a drug displaying antitumor efficacy against NB (17,18). Ponatinib proved to inhibit the FGFR1-activated signaling pathway and enhance the cytotoxic effects of doxorubicin on NB cells (18).…”
Section: Discussionmentioning
confidence: 62%
“…Pazopanib potently inhibits VEGF‐induced phosphorylation of VEGFR2 in HUVEC cells with IC 50 of 8 nM. Ponatinib inhibits multiple RTKs implicated in pathological angiogenesis such as PDGFRα, VEGFR‐2, FGFR1, and Src . It exhibited a significant antiangiogenic effect and was approved in 2012.…”
Section: Recent Advances In Small‐molecule Antiangiogenic Agentsmentioning
confidence: 99%
“…Ponatinib inhibits multiple RTKs implicated in pathological angiogenesis such as PDGFR , VEGFR-2, FGFR1, and Src. 156 It exhibited a significant antiangiogenic effect and was approved in 2012. Linifanib is a potent ATP-competitive inhibitor for VEGFR-2, Flt-1/3, and PDGFR .…”
Section: Multitarget Rtkis As Antiangiogenic Agentsmentioning
confidence: 99%
“…The mechanisms of action of PON include the regulation of several intracellular signaling pathways, such as STAT3, PI3K/AKT, and ERK, which are all involved in supporting tumor cell proliferation and survival [ 7 ]. However, some studies have found an increased rate of resistance to PON in either pre-clinical or clinical settings [ 8 10 ], and a similar finding may therefore be possible in neuroblastoma, in which the efficacy of PON emerged from both in vitro and in vivo pre-clinical assessments [ 11 , 12 ]. In a previous high-throughput screening (HTS) study, among 349 compounds tested, PON gave the best results in impeding the growth of neuroblastoma cells [ 13 ].…”
Section: Introductionmentioning
confidence: 98%